2020
DOI: 10.1186/s13014-019-1452-4
|View full text |Cite
|
Sign up to set email alerts
|

Definitive chemoradiotherapy in patients with squamous cell cancers of the head and neck - results from an unselected cohort of the clinical cooperation group “Personalized Radiotherapy in Head and Neck Cancer”

Abstract: BackgroundDefinitive chemoradiotherapy (dCRT) is a standard treatment for patients with locally advanced head and neck cancer. There is a clinical need for a stratification of this prognostically heterogeneous group of tumors in order to optimize treatment of individual patients. We retrospectively reviewed all patients with head and neck squamous cell carcinoma (HNSCC) of the oral cavity, oropharynx, hypopharynx, or larynx, treated with dCRT from 09/2008 until 03/2016 at the Department of Radiation Oncology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 44 publications
1
20
1
1
Order By: Relevance
“…Other studies have also found no link between T stage and local recurrence rate, finding instead that primary tumor volume may be a better predictive tool [ 15 - 18 ]. Our study showed a strong correlation between advanced nodal status (N2-3) and outcomes, which has been corroborated by a number of studies finding links between nodal stage and volume with survival and control outcomes [ 15 , 18 , 19 ]. Finally, there is additional data supporting the use of PET imaging, including metabolic tumor volume and maximum SUV, as a predictor for larynx preservation and OS [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 87%
“…Other studies have also found no link between T stage and local recurrence rate, finding instead that primary tumor volume may be a better predictive tool [ 15 - 18 ]. Our study showed a strong correlation between advanced nodal status (N2-3) and outcomes, which has been corroborated by a number of studies finding links between nodal stage and volume with survival and control outcomes [ 15 , 18 , 19 ]. Finally, there is additional data supporting the use of PET imaging, including metabolic tumor volume and maximum SUV, as a predictor for larynx preservation and OS [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 87%
“…In regions associated with a high risk of existing or postoperatively remaining tumor cells, the dose was 60 to a maximum of 66 Gy, and in areas of physiological anatomical lymphatic drainage, the dose was about 50 Gy. For postoperative patients with high-risk features and for patients with advanced disease who received primary RT, concomitant systemic therapy (CRT) was applied [ 30 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although the addition of the cytotoxic compound cisplatin to radiotherapy (RT) improved 5-year PFS from 36% to 47% and 5-year overall survival (OS) from 40% to 53%, it also caused a significant increase in severe functional mucosal adverse effects from 21% to 40% [2]. Due to the increased risk of side-effects, full compliance of chemoradiotherapy (CRT) is seen in only about two-thirds of the initially eligible patients [3][4][5]. Ongoing research evaluates and compares different systemic treatment regimens and novel therapeutic approaches with consideration of potential patient-related (i.e., HPV status) and treatment-related factors (i.e., dose regimen) in order to improve treatment tolerance and survival in LA-HNC patients.…”
Section: Introductionmentioning
confidence: 99%